The Impact of Switching on the Dynamics of Prey-Predator Model for a Switching Tendency - Naji, Raid Kamel; Majeed, Azhar Abbas (Al-Nahrain Journal of Science, 2018)
In this paper, a mathematical model, consists from a stage structured predator interacting with prey which is assumed to live in two distinct habitats, and the predator has the tendency to switch among these habitats, is proposed and analyzed. The existence and uniqueness of the solution of the proposed model are discussed. The existence and the stability analyses of all possible equilibrium points are studied. Because of difficulty of analytical computation the global stability of these equilibrium points and the persistence of the model will be studied numerically.